Multi-channel marketing, branding and retail design : new challenges and opportunities - McIntyre, Charles, 1955-; Melewar, T. C.; Dennis, Charles
Recently, many researchers have found that their work crosses the borders of design, branding and marketing. This orientation finds itself in contrast to the generally discipline-delineated world of academic journal publishing where cross-sector studies often find difficulties in acceptance (design-based work in marketing being particularly poorly represented). This unique book focuses upon service design, including retail and multi-channel marketing matters pertinent to the current age where physical contact with consumers has resurfaced as an enduring part of the marketing and branding landscape - complementary to online and virtual worlds. The span of the text goes from what may be regarded as micro-environmental issues of type design and the semiotics of brand meanings towards macro-environmental concerns of city design and ecological threat, all relative to living within any world (and all worlds) that businesses and consumers may co-create or are invited and welcomed to in their own multi-layered experience.